Clinical practice guidance for Sjögren's syndrome in pediatric patients (2018) – summarized and updated. Issue 2 (4th March 2021) - Tomiita, Minako; Kobayashi, Ichiro; Itoh, Yasuhiko; Inoue, Yuzaburo; Iwata, Naomi; Umebayashi, Hiroaki; Okamoto, Nami; Nonaka, Yukiko; Hara, Ryoki; Mori, Masaaki
Abstract: There are a considerable number of pediatric patients with Sjögren's syndrome (SS); however, SS is generally considered rare among children. Pediatric patients with SS report fewer sicca symptoms; therefore, many are under-diagnosed and cannot access appropriate medical management. Therefore, we propose a newly developed guidance for the diagnosis, treatment, and management of pediatric SS, including epidemiology, clinical features, and diagnostic examination methodology. The aim of this guidance was to standardize the medical care of pediatric SS in Japan, and we published the Japanese version by YODOSHA in 2018. This article is the English version, which is summarized and updated. This guidance will need to be revised in the near future as additional clinical data become available.